Needs Analysis of Educational Game Tools Based on Tri Hita Karana Values to Improve Early Childhood Prosocial Behavior - Bayu Indrayasa, Kadek; Sumadi, Tjipto; Nurani, Yuliani (International Proceedings of Nusantara Raya, 2024)
This research focuses on the needs analysis of Tri Hita Karana value-based educational game tools in an effort to improve early childhood prosocial behavior. Prosocial behavior, which includes cooperation, sharing, and empathy, is an important aspect of children's social development that must be developed early on. However, initial observations at Kindergarten X showed that children still have difficulty in developing optimal prosocial behavior. Learning that has been done focuses more on cognitive aspects, while social interactions and activities that can support the development of prosocial behavior are still minimal.The research method used was descriptive qualitative, with data collection techniques through semi-structured interviews, non-participant observation, and documentation studies. The research subjects consisted of teachers, principals, and students in group B of X Kindergarten. The collected data were analyzed using content analysis techniques to identify the needs of educational game tools that can support the development of children's prosocial behavior. The proposed game tools are based on Tri Hita Karana values, namely Parahyangan (harmonious relationship with God), Pawongan (harmonious relationship between fellow humans), and Palemahan (harmonious relationship with nature), which are integrated in the form of constructive games that encourage collaboration. The results showed that the current educational game tools do not fully support the development of children's prosocial behavior. Therefore, innovation is needed in the development of educational game tools that integrate local cultural values such as Tri Hita Karana. The implementation of this tool is expected to be an effective solution in improving early childhood prosocial behavior through a fun and meaningful approach. Thus, this research makes an important contribution in the field of early childhood education, and emphasizes the importance of integrating local cultural values in learning to form good character in children.